Introduction. The Himalayas from its edges: networks, identities and place-making - Dibyesh Anand; Swargajyoti Gohain; Nitasha Kaul; Sayantani Mukherjee (European Bulletin of Himalayan Research)
While the perspectives of sovereign nation-states have tended to dominate how the Tibeto-Himalayan region has been shaped, viewed and lived in the last century, we argue for adoption of multidisciplinary perspectives that focus on flows and interactions rather than the limited frames of state-centred exchanges. Collating empirically grounded studies from different parts of the Himalayas, this special issue highlights the cross-border networks, negotiated identities and politics of place that are directly and indirectly enabled by state practices and are enacted in the lives of the people in the region. This issue offers a critical understanding of the tangled role of cultural, material, political and economic factors that have informed historical and contemporary processes in the Himalayas. In this introductory paper, we highlight the Himalayas as a productive site of contestation before identifying some of the connections and ruptures that mark it. A useful way to understand the region and its peoples is through the foregrounding of networks, identities and place-making that mark its lived realities.